(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current research aims at knowing investigating the degree to which principals of secondary schools in Latakia practice conflict management methods from the point of view of their assistant Principals of school, as well as their differences in the dependency of sex variables, scientific qualification, and number of years of experience. Using the descriptive analytical curriculum, the research sample was formed from all the assistant principals of secondary schools in Latakia, numbering (76) assistants and assistants. To achieve the research objectives, a questionnaire consisting of (32) items was prepared spread over (4) conflict management methods (cooperation method, coercion, settlement method, avoidance method), validated and stable, and the data were processed using the computer statistical software. (SPSS) The research has found several results, the most important of which were are: - The degree to which principals of secondary schools in Latakia practice conflict management methods from the point of view of their aides is regressive as follows (method of cooperation, method of settlement, method of coercion, avoidance(. - There are no statistically significant differences in conflict management methods among the members of the research sample depending on the variable of scientific qualification except after cooperation. - There are no statistically significant differences in conflict management methods among the members of the research sample depending on the variables of the number of years of experience.